Peningkatan Keterampilan Membaca Pemahaman dengan Pemanfaatan Aplikasi Let’s Read pada Siswa Kelas V Sekolah Dasar - Saputri, Nurwanda; Ritonga, Rudi (Academy of Education Journal, 2024)
This study aims to improve reading comprehension skills by utilizing the Let's Read application for fifth grade elementary school students. This study used a classroom action research method involving 32 students who were fifth grade elementary school students. Data were collected through observation, interviews, and performance tests. Based on the results of observations and data analysis during the implementation of reading comprehension tests in the pre-cycle, the average score was 69.13. In cycle I by implementing Let's Read media the average value became 76.98. In cycle II the average value became 86.22. Thus, this research can be said to be successful because it has reached the success indicator of 78 test results from reading comprehension. This research can improve reading comprehension skills by utilizing the Let's Read application for fifth grade elementary school students.